OPTIMALISASI PROSEDUR OPERASIONAL BERDASARKANSERVICE OPERATION SESUAI SIKLUS INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY V.3 - Triana Wulandari (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
This study attempts to find out how best in optimizing operational handling technology in a company. Any company that uses technology as bagain of business can optimize it have to be investment in technology and the opportunities greater sustainability. Way as on the optimizing operational is to provide several a standard procedure that is we can the adoption of itil v3 so that a groove of work and evaluation can be executed with optimal.With the introduction of the optimization of workflow then it is hoped the process of change can be detected faster so that the sustainability of. petrifaction in his business.The procedures to be furnished event management, among others incident management, fulfillent, request the problem of management and permissions.